Laser calorimetry for assessment of melting behaviour in multi-walled carbon nanotube decorated aluminium by laser powder bed fusion. Issue 1 (2020) - Clare, Adam T.; Reynolds, William J.; Murray, James W.; Aboulkhair, Nesma T.; Simonelli, Marco; Hardy, Mark; Grant, David M.; Tuck, Chris
Abstract: Material development for powder bed fusion is critical to enhance the utility of the process. Establishing process parameters for new materials limits the rate at which process performance can be appraised. Adapted laser calorimetry is a useful technique for rapid material screening. Here, multi-body feedstocks which have the potential to improve laser coupling and mechanical properties of structures (Al + multi-walled carbon nanotubes) are investigated to demonstrate the flexibility of laser calorimetry for understanding consolidation and heat transfer phenomena in powder bed fusion. It is shown that the modifications to powder surface condition/chemistry improve consolidation behaviour in this case.